Identifying the World Health Organization's fifth moment for hand hygiene: Infection prevention in the operating room. Issue 1 (January 2020) - Smith, Fiona; Lee, Karen; Binnie-McLeod, Eleanor; Higgins, Mark; Irvine, Elizabeth; Henderson, Angela; Orr, Ann; Clark, Fiona; Spence, Joanne
Background: The World Health Organization have designed the fifth of their '5 moments' for hand hygiene to account for microbial transfer from patients to equipment in a narrow area around that patient, known as the patient zone. The study was prompted by emerging local confusion about application of the patient zone in the operating room (OR). Aim/Objectives: In two phases, we aimed to create a '5 moments' style poster displaying an OR patient zone: phase 1, quantify equipment, in direct contact with the patient and, touched by non-scrubbed staff immediately after touching the patient; and phase 2, categorise equipment identified in phase 1 into patient zone and healthcare zone. An objective is to produce a '5 moments' poster for the OR. Methods: The first phase used non-participant direct overt observation. In phase 2, phase 1 data were collaboratively assigned to patient zone or healthcare zone. Photography and graphic design were used to produce the OR '5 moments' poster. Results: In 11 full-length surgeries, 20 pieces of equipment were in direct contact with the patient and 57 pieces of equipment were touched. In phase 2, a '5 moments' poster showing an OR patient zone was designed. Discussion: Content of the patient zone was identified and displayed in a novel resource. Having shared understanding of the patient zone has potential to sustain hand hygiene compliance and equipment cleaning in the OR. Conclusion: Limitations in methods were balanced by collaboration with frontline staff. The study has been used as a teaching tool in the OR and similar settings.